APLIKASI DAN IMPLIKASI TEORI BEHAVIORISME DALAM PEMBELAJARAN (Analisis Strategis Inovasi Pembelajaran) - Muh. Hizbul Muflihin (Khazanah Pendidikan, 2009)
Learning and teaching are inseparable but not identical. Learning is more descriptive, while teaching more prescriptive. From behavioristic point of view, a teacher should be able to create an atmosphere which enables students to build the expected competence. When this is achieved, it should be followed with reinforcement to make it part of students memory. Key words : learn, behavioristic learning, inovation learning